A hedonist manifesto : the power to exist - Onfray, Michel, 1959- (Insurrections., 2015)
Michael Onfray passionately defends the potential of hedonism to resolve the dislocations and disconnections of our melancholy age. In a sweeping survey of history's engagement with and rejection of the body, he exposes the sterile conventions that prevent us from realizing a more immediate, ethical, and embodied life. He then lays the groundwork for both a radical and constructive politics of the body that adds to debates over morality, equality, sexual relations, and social engagement, demonstrating how philosophy, and not just modern scientism, can contribute to a humanistic ethics. Onfray.